Reliability of dynamic fluoroscopy for medial elbow stability in the presence of radial head resection: a cadaveric study - Bergmann, Moritz; Barbari, Jan el; Porschke, Felix; Grützner, Paul Alfred; Gühring, Thorsten; Schnetzke, Marc (Obere Extremität, 2020)
The aim of this study was to examine whether dynamic fluoroscopy is reliable for assessment of medial elbow stability in the presence of radial head resection and different stages of medial collateral ligament (MCL) dissection in a cadaveric elbow model.
Gesehen am 08.12.2021